UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Hasrat, Hasrat (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
The purpose of this study is to describe the efforts in improving science learning outcomes using the cooperative learning model type Student Teams Achievement Divisions (STAD) in class IV students of  SDN 05 Rantau Alai . The method used in this research is Classroom Action Research (CAR). In accordance with the Classroom Action Research (CAR) model, the research procedure consists of 4 stages, namely: (1) planning, (2) implementation, (3) observation, (4) reflection. This research consisted of pre-cycle, first cycle and second cycle. The results of this study indicate an increase in science learning outcomes for fourth grade students of SDN 05 Rantau Alai. This can be seen from the results of cycle I to cycle II, from a 60% percentage increase to 90% with the good group category